The evolution of religion, religiosity, and theology: a multi-level and multi-disciplinary approach - Feierman, Jay R.; Oviedo, Lluis (Routledge new critical thinking in religion, theology and biblical studies, 2020)
Introduction: a multi-level and multi-disciplinary approach to understanding religion and its evolution / Lluis Oviedo -- Cultural evolution, biology, and the case of religion / HansgoÌ⁸rg Hemminger -- The evolutionary biology of religion specific beliefs and inter-religious conflict / Jay R. Feierman -- Sex and the evolution of spirituality / Daniel Cohen -- The biological basis for religion and religion's evolutionary origins / Donald Broom -- A history of the evolution of religion: from religion to religiosity to the processes of believing / Hans-Ferdinand Angel -- The processes of believing in religion's evolution: a cognitive neuroscience hypothesis / RuÌ⁸diger J. Seitz -- Near-death and out-of-body experiences in sensing the divine: one foundational role in religion's evolution / Michael N. Marsh -- Awe as a meaning-making emotion: on the evolution of awe and the origin of religions / Elliott Ihm, Jonathan Schooler, Michael van Elk and Ray Paloutzian -- Whence this need for salvation? Childhood corporal punishment and the cultural evolution of religious myth / Benjamin Abelow -- What a theological appropriation of cognitive linguistics' blending theory brings to a scientific understanding of the evolution of religion / Robert Masson -- The evolution of religiosity: a theologian's view / Christopher C. Knight -- Neoteny and homo religiosus: brain evolution and the emergence of the capacity for spirituality / William Ulwelling -- Emotions and the evolution of the belief in God / Christian Early -- The evolution of hunter-gather religion: issues and debates among the San bushmen of southern Africa / Robert Hitchcock -- Bones, pigments, art and symbols: archaeological evidence for the origins of religion / Anne Solomon -- Every kingdom divided against itself: moral laws and the persecution of Christians in the evolution of Christianity / Laura Betzig.